Telekonsultasi Klinis: Etika, Disiplin, dan Hukum Kedokteran - Dony Septriana Rosady; Lutfan Lazuardi; Siswanto Sastrowijoto (Masyarakat Hukum Kesehatan Indonesia, 2022)
The COVID-19 pandemic has had an impact and changed various aspects of life in Indonesia. Adaptation efforts are carried out to answer the needs of the community in various sectors during the COVID-19 pandemic. Changes have also occurred in the health care sector. The practice of teleconsultation is carried out as an alternative form of medical practice in response to the need for safe access to health services for the community by utilizing information and communication technology. The research was conducted with a qualitative approach. The research was conducted as a clinical teleconsultation case study at UPT Puskesmas Sukarasa. Data were collected using interviews with 2 main participants and 10 supporting participants, observations were made on the teleconsultation practice that was carried out and document studies on documentation and applicable regulations. The results showed that the clinical teleconsultation practice carried out by UPT Puskesmas Sukarasa had applied the applicable rules, legal norms, and medical disciplines. Compliance with ethical rules, legal norms, and medical discipline is an effort to ensure the fulfilment of patient safety in medical practice.